FORECASTING THE USE OF OKE JACK COMPANY’S ONLINE TRANSPORTATION IN MEDAN USING THE CHENG FUZZZY TIME SERIES METHOD - Sari, Dinda; Dur, Sajaratud; Rakhmawati, Fibri; Anjelina, Repina (Journal of Mathematics and Scientific Computing With Applications, 2022)
Transportation is an activity to move goods or people from one place to another. At present, transportation is very much needed by all groups to carry out an activity. Along with the development of the times and with the development of the times and with the existence of an internet, now many enterpreneurs are opening a business such as online transportation. This study uses the Fuzzy Time Series Cheng method in his research to see how accurate the model is to predict the future period. The results of the research using the Fuzzy Time Series Cheng method on the five service features in the Oke Jack, it was found that some of these service features resulted in MAPE error values below 10%, which is the best measure.